Individuals with autism show non-adaptive relative weighting of perceptual prior and sensory reliability. (November 2022) - Binur, Nahal; Hel-Or, Hagit; Hadad, Bat-Sheva
Modulation in sensory-perceptual processing is a known characteristic of autism, although the underlying mechanism is debated. A prevailing account is formulated in Bayesian terms, where either a reduced prior or reduced noise in the measurement (sensory input) may account for the modulated perception as expressed by the posterior distribution. However, research has shown that individuals with autism use priors in some conditions, and to the same extent as neurotypicals, while other studies fail to show enhanced sensory sensitivity in these individuals. We asked whether the modulated prior effects on perception may arise from non-adaptive relative weighting of priors to sensory reliability. We employed a Two-alternative forced choice (2AFC) width discrimination task, using the width–height illusion, which is based on a long-term acquired bias, where a taller rectangle is typically perceived as thinner than a shorter one. The measurement was manipulated by adding Gaussian blur on the vertical edges of the rectangles. Typically developed individuals displayed the expected increase in bias as a function of noise in the measurement. High-functioning individuals with autism exhibited typical perceptual resolutions and similar susceptibility to the illusion. However, the relative weighting of the perceptual bias and the sensory input differed in their effect on the two groups. Individuals with autism showed a non-adaptive, consistent bias across the different degrees of sensory noise, while typically developed individuals displayed monotonically increasing biases. Cluster analyses showed that this difference in the relative weighting between the groups was preserved regardless of the overall illusion magnitude displayed by individuals in each cluster. Lay abstract: Unique perceptual skills and abnormalities in perception have been extensively demonstrated in those with autism for many perceptual domains, accounting, at least in part, for some of the main symptoms. Several new hypotheses suggest that perceptual representations in autism are unrefined, appear less constrained by exposure and regularities of the environment, and rely more on actual concrete input. Consistent with these emerging views, a bottom-up, data-driven fashion of processing has been suggested to account for the atypical perception in autism. It is yet unclear, however, whether reduced effects of prior knowledge and top-down information, or rather reduced noise in the sensory input, account for the often-reported bottom-up mode of processing in autism. We show that neither is sufficiently supported. Instead, we demonstrate clear differences between autistics and neurotypicals in how incoming input is weighted against prior knowledge and experience in determining the final percept. Importantly, the findings tap central differences in perception between those with and without autism that are consistent across identified sub-clusters within each group.